Strain-specific properties and T cells regulate the susceptibility to papilloma induction by Mus musculus papillomavirus 1. - Alessandra Handisurya; Patricia M Day; Cynthia D Thompson; Michael Bonelli; Douglas R Lowy; John T Schiller (PLoS Pathogens)
The immunocytes that regulate papillomavirus infection and lesion development in humans and animals remain largely undefined. We found that immunocompetent mice with varying H-2 haplotypes displayed asymptomatic skin infection that produced L1 when challenged with 6×1010 MusPV1 virions, the recently identified domestic mouse papillomavirus (also designated "MmuPV1"), but were uniformly resistant to MusPV1-induced papillomatosis. Broad immunosuppression with cyclosporin A resulted in variable induction of papillomas after experimental infection with a similar dose, from robust in Cr:ORL SENCAR to none in C57BL/6 mice, with lesional outgrowth correlating with early viral gene expression and partly with reported strain-specific susceptibility to chemical carcinogens, but not with H-2 haplotype. Challenge with 1×1012 virions in the absence of immunosuppression induced small transient papillomas in Cr:ORL SENCAR but not in C57BL/6 mice. Antibody-induced depletion of CD3+ T cells permitted efficient virus replication and papilloma formation in both strains, providing experimental proof for the crucial role of T cells in controlling papillomavirus infection and associated disease. In Cr:ORL SENCAR mice, immunodepletion of either CD4+ or CD8+ T cells was sufficient for efficient infection and papillomatosis, although deletion of one subset did not inhibit the recruitment of the other subset to the infected epithelium. Thus, the functional cooperation of CD4+ and CD8+ T cells is required to protect this strain. In contrast, C57BL/6 mice required depletion of both CD4+ and CD8+ T cells for infection and papillomatosis, and separate CD4 knock-out and CD8 knock-out C57BL/6 were also resistant. Thus, in C57BL/6 mice, either CD4+ or CD8+ T cell-independent mechanisms exist that can protect this particular strain from MusPV1-associated disease. These findings may help to explain the diversity of pathological outcomes in immunocompetent humans after infection with a specific human papillomavirus genotype.